Top Quark Physics at Hadron Colliders - Quadt, Arnulf; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2007)
More than ten years after its discovery, still relatively little is known about the top quark, the heaviest known elementary particle. The present extensive survey summarizes and reviews top-quark physics based on the precision measurements at the Fermilab Tevatron Collider, as well as the sensitivity of these experiments to new physics. Finally, an outlook on top quark physics at the Large Hadron Collider is given.
Introduction -- Top Quark Production and Decay at Hadron Colliders -- Accelerator and Detectors -- Measurement of the ttbar Production Cross Section at the Tevatron -- Search for Single Top Quark Production -- Top Quark Interactions to Gauge Bosons -- Fundamental Properties of the Top Quark -- Anomalous Top Quark Production -- Anomalous Top Quark Decays -- New Physics in Events with ttbar Topology -- Top Quark Physics at the LHC -- Summary.
Keywords: Atoms; Physics; Elementary particles (Physics).; Quantum field theory; Physical measurements; Measurement .; Atomic, Molecular, Optical and Plasma Physics; Elementary Particles, Quantum Field Theory; Measurement Science and Instrumentation